Towards a framework for the global wine tourism system - Santos, Vasco (2021)
Purpose – Wine tourism has stood out as a very recognized and valid tourism and marketing segment, growing worldwide and urging the complex needed advances on wine tourism practices performance. This paper aims to develop a new framework strictly applied to the global wine tourism system, taking into account emerging and future constructs and dimensions that precede and consequence it. Design/methodology/approach – The systematic mapping study (SMS) was adopted as the selected research methodological approach, both to analyze and to structure a broad research field concerning methods, designs and research, focuses on the papers published in reliable academic databases such as Emerald, ProQuest, Sage, Science Direct, Scopus, Wiley, Web of Science, Taylor and Francis and Wiley were properly selected and analyzed. Findings – The following four dimensions were found to comprise the global framework of the wine tourism system: (1) support features (governance, public policies and economic investment; supply development; physical and capacity conditions; requirements of health safety; opinion makers and leaders: managers/ stakeholders/players/marketers and benchmarking and value chain); (2) innovation ecosystem (profile of the new generations of wine tourists; virtual and augmented reality: digital and hybrid wine events; smart wine tourism companies; digital channels and platforms: blogs, websites, applications; wine tourism creative activities for all [from kids to seniors] and sustainable and ecologic wine tourism practices); (3) wine tourism experience dimensions (storytelling; involvement; winescape; attachment; emotions and sensory) and (4) behavioural intentions (satisfaction; loyalty; and WoM). Research limitations/implications – The framework still needs to be empirically applied in wine tourism settings to enrich tourists’ robustness in cross-cultural wine tourism experiences, covering a wider spread of abroad wine tourism destinations and products. Practical implications – This framework is a useful tool and becomes vital to their continued success, as a key reference of wine tourism management and marketing. As a wine tourist’s visitation frequency plays a role in his/her travel motives, product and service quality of tour packages must be improved and monitored. Originality/value – This is the first research study to demonstrate the combined use of the main domains forming the wine tourism system within a global perspective, covering of the most critical aspects.